Heliconia ‘Golden Torch’ postharvest: stem ends cutting and renewing vase water benefits - Folha, Wladiney Rodrigues; Souza, Rafaela Ribeiro; Amaral, Genilda Canuto; Silva, Alcilane Arnaldo; Carvalho, Jullyanna Nair; Beckmann Cavalcante, Márkilla Zunete (Ornamental Horticulture, 2016)
The postharvest longevity is one of the main aspects that should be considered in the production of cut flowers and is a pre-requisite for product quality and marketing success. However, cut flowers are highly perishable products that need to be treated and stored to maintain its quality and value. This study aimed to assess Heliconia psittacorum ‘Golden Torch’ inflorescences postharvest longevity, submitted to periodic stem ends cutting and vase water renewal. The experimental design was a completely randomized 3x2 factorial, corresponding to the stem ends cuts (1 cm; without cutting; cutting at 24 hours; cutting at 48 hours) and water renewal (with and without renewal), with four repetitions. The assessed variables were: water uptake by flower stems (WUFS); loss of fresh stem mass (LFSM); dry matter of flower stems (DMFS) and postharvest longevity (PHL). The stem cut significantly influenced WUFS and LFSM. However, the water renewal factors affected all variables, while the interaction between factors (stem cuts x water renewal) only influenced PHL. The cuts at the stem base of Heliconia ‘Golden Torch’ procedures enable the restoration of water potential and this practice, associated with water renewal during storage allows greater tissues hydration, maintaining the postharvest quality.